2022
DOI: 10.1159/000523838
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Mild Acute Ischemic Stroke with Large-Vessel Occlusion: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> The functional prognosis of mechanical thrombectomy (MT) for mild acute ischemic stroke (AIS) with large-vessel occlusion (LVO) is controversial. To explore a more precise estimation, a meta-analysis was conducted. <b><i>Methods:</i></b> The relevant studies were identified by searching PubMed, Embase, Web of Science, and Cochrane Collaboration Database until October 2021. The pooled analysis, subgroup analysis, sensitivity analysis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In another meta-analysis that compared EVT and medical management in patient with AIS, baseline NIHSS scores ≤5, and LVO, EVT did not improve the functional outcomes among the patients 16. Similarly, an international multicenter study and meta-analysis documented no obvious difference in clinical outcomes between mechanical thrombectomy and medical management in patients with AIS and mild-deficit emergency LVO 31.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In another meta-analysis that compared EVT and medical management in patient with AIS, baseline NIHSS scores ≤5, and LVO, EVT did not improve the functional outcomes among the patients 16. Similarly, an international multicenter study and meta-analysis documented no obvious difference in clinical outcomes between mechanical thrombectomy and medical management in patients with AIS and mild-deficit emergency LVO 31.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Zhao et al reported similar functional outcomes after 3 months of EVT and medical treatment in patients with mild stroke (NIHSS score <5 or < 8) and LVO; furthermore, those who underwent EVT had an increased risk of symptomatic ICH 15. Another recent meta-analysis, which included only patients with baseline NIHSS scores ≤5, suggested that mechanical thrombectomy might not be related to the functional prognosis of patients with mild stroke and LVO 16. However, most of the aforementioned studies included patients with posterior circulation vessels and lacked propensity score (PS)-based methods to control confounding factors.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, 8.6% of LAVO patients had no unilateral arm paresis, leading to false negative results. However, these patients were mostly mildly affected, making the decision for or against thrombectomy a matter of discussion (Hou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%